Methoxyacetic acid inhibits histone deacetylase and impairs axial elongation morphogenesis of mouse gastruloids in a retinoic acid signaling‐dependent manner. Issue 14 (4th June 2020) - Li, Aileen S. W.; Marikawa, Yusuke
Abstract: Background: Teratogenic potential has been linked to various industrial compounds. Methoxyacetic acid (MAA) is a primary metabolite of the widely used organic solvent and plasticizer, methoxyethanol and dimethoxyethyl phthalate, respectively. Studies using model animals have shown that MAA acts as the proximate teratogen that causes various malformations in developing embryos. Nonetheless, the molecular mechanisms by which MAA exerts its teratogenic effects are not fully understood. Methods: Gastruloids of mouse P19C5 pluripotent stem cells, which recapitulate axial elongation morphogenesis of gastrulation‐stage embryos, were explored as an in vitro model to investigate the teratogenic action of MAA. Morphometric parameters of gastruloids were measured to evaluate the morphogenetic effect, and transcript levels of various developmental regulator genes were examined to assess the impact on gene expression patterns. The effects of MAA on the level of retinoic acid (RA) signaling and histone deacetylase activity were also measured. Results: MAA reduced axial elongation of gastruloids at concentrations comparable to the teratogenic plasma level (5 mM) in vivo. MAA at 4 mM significantly altered the expression profiles of developmental regulator genes. In particular, it upregulated the RA signaling target genes. The concomitant suppression of RA signaling using a pharmacological agent alleviated the morphogenetic effect of MAA. MAA at 4 mM also significantly reduced the activity of purified histone deacetylase protein. Conclusions: MAA impaired axial elongation morphogenesis in a RA signaling‐dependent manner in mouse gastruloids, possibly through the inhibition of histone deacetylase.